Safety and Efficacy of Botulinum Toxin A in Children Undergoing Lower Limb Lengthening and Deformity Correction: Results of a Double-blind, Multicenter, Randomized Controlled Trial. Issue 1 (January 2016) - Hamdy, Reggie C.; Montpetit, Kathleen; Aiona, Michael D.; MacKenzie, William G.; van Bosse, Harold J.P.; Narayanan, Unni; Raney, Ellen M.; Chafetz, Ross S.; Thomas, Susan E.S.; Weir, Shannon; Gregory, Shelley; Yorgova, Petya; et al.
Abstract : Background: Lengthening of the lower limb is a complex procedure in which pain management and complications such as pin-site infections and muscle contractures impact the family and affect the child's quality of life. As a result, the paralytic and antinociceptive actions of neurotoxins may be indicated in managing these complications; however, few studies have explored ways to improve outcomes after lengthenings. The objective of this study was to evaluate the safety and efficacy of botulinum toxin A (BTX-A) in children undergoing lower limb lengthenings and deformity correction. Methods: Participants with a congenital or acquired deformity of the lower extremity requiring surgery to one limb were randomized to receiving either BTX-A as a single dose of 10 units per kilogram body weight, or an equivalent volume of saline solution. Pain, medication, quality of life, and physical function were assessed at different time-points. Adverse events were recorded in all participants. T test and χ 2 tests were used to compare potential differences across both groups. Results: Mean age of the 125 participants was 12.5 years (range, 5 to 21 y), and lengthenings averaged 4.2 cm. Maximum pain scores on day 1 postoperatively were lower in the BTX-A group ( P =0.03) than in the placebo group, and remained significant favoring botox when stratifying by location of lengthening (femur vs. tibia). Clinical benefits for BTX-A were found for 3 quality of life domains at mid-distraction and end-distraction. When stratifying according to location of lengthening, there were significantly fewer pin-site infections in the tibia favoring botox ( P =0.03). The amount of adverse events and bone healing indices were no different in both groups. Conclusions: The clinical differences in quality of life, the lower pain on the first postoperative day, and the lower number of pin-site infections in the tibia favoring BTX-A support its use as an adjunctive treatment to the lengthening process. The detailed analyses of pain patterns help inform families on the pain expectations during lower limb lengthenings. The amount of adverse events were no different in both groups, and bone healing rates were similar, indicating that the use of BTX-A in children undergoing limb lengthening and deformity correction is safe. Level of Evidence: Level I.